(untitled) (Acta Polytechnica CTU Proceedings, 2015)
I present an overview of the ongoing observational programs utilizing the Southern African Large Telescope (SALT), focussing on magnetic Cataclysmic Variables and Low Mass X-ray Binaries. SALT’s instruments and capabilities are well suited to time resolved studies of the accretion phenomena exhibited in these systems. Initial observations, using SALTICAM, have been used to derive high time resolution ( 100ms) eclipse light curves, with high signal-to-noise, of Polars. Recently this work has been extended to time resolved spectroscopic studies, utilizing the SALT Robert Stobie Spectrograph (RSS), allowing an opportunity to probe how the emission lines change during eclipse. A program to search for and characterize quasi-periodic oscillations (QPOs) in magnetic CVs using the SAAO 1.9-m telescope, begun in 2012, has been expanded to include observations with a photon counting camera (BVIT) on SALT. A multi-longitude campaign involving SALT, other SAAO facilities plus the ESO NTT, was carried out in March/April 2012 on the enigmatic gamma ray source, XSS J12270–4859, which has revealed the that system exhibits spectral line variations, from absorption to emission, seemingly over timescales of < 1 h.